Propagation of Sealing Wax Palm, Cyrtostachys Renda Blume, Using in Vitro Techniques - Md. Marzuki, Siti Maisarah (1997)
A series of experiments on the culture of vegetative tissues and embryos of Cyrtostachys renda Blume were conducted to explore the possibility of in vitro culture as an alternative system of propagation. Isozyme typing of the vegetative tissues used as explants was also carried out. Unemerged leaf tissue of about 1cm with petiole attached and probably including shoot (L1), was used as explant. The preceding two 1-cm leaf sections before Ll were also used as exalants. However,the youngest tissue (L1) used was least-proned to browning and survived in culture where as the preceding two sections died in culture. Three different culture media were tested,namely modified Murashige and Skoog (MMS),oil palm medium(OPM) and Woody Plant Medium (WPM). MMS was found to be suitable for the explant of C. renda whereas OPM and WPM were found to be unsuitable.